An Optimal Threshold Strategy in the Two-Envelope Problem with Partial Information. (30th January 2018) - Egozcue, Martin; Fuentes García, Luis
Abstract : In this paper we propose a strategy that gives an optimal lower bound of the average gain for the two-envelope problem within the McDonnell and Abbott (2009) and McDonnell et al. (2011) framework. We obtain this result with partial information about the probability distribution of the envelope's contents.